Effect of type traits on functional longevity of Czech Holstein cows estimated from a Cox proportional hazards model - Zavadilová, L; Němcová, E; Stípková, M (Journal of dairy science, 2011)
Relationships between conformation traits and functional longevity in Holstein cows were evaluated using survival analysis. Functional longevity was defined as the number of days between the first calving and culling; that is, length of productive life. The data set consisted of 116,369 Holstein cows that first calved from 2003 to 2008. All cows used in the analysis were scored for conformation between d 30 and d 210 of their first lactation. The data included 48% censored records. Analyses were done separately for 20 linear descriptive type traits, 6 composite traits, and height at sacrum measured in centimeters. Cox proportional hazard models were fitted to analyze data. The hazard function was described as the product of a baseline hazard function and the time-independent effects of age at first calving and sire (random), and the time-dependent effects of stage of lactation and lactation number, herd, year and season, herd size, and 305-d milk production. The strongest relationship between a composite trait and functional longevity was for dairy form, followed by udder and final score. Among the descriptive type traits, the strongest relationships with longevity were found for body condition score, angularity, traits related to udder attachment, and udder depth. Foot and leg traits showed substantially lower effect on functional longevity, and the effect of foot angle was minimal. Functional longevity declined with decreased body condition score of cows. Cows with deep udders had significantly lower functional survival compared with cows with shallow udders. In addition, weak central ligament was associated with significant reduction of cow longevity. For dairy form and angularity, cows classified as very good were the worst with respect to longevity, whereas cows classified as poor were the best. An intermediate optimum was evident for rear legs rear view and rear legs set (side view), whereas cows with sickled legs had lower longevity than cows with straighter legs.
Keywords: Animals; Quantitative Trait, Heritable; Czech Republic; Mammary Glands, Animal; zvířata; proporcionální rizikové modely; mléčné žlázy zvířat; dlouhověkost; Longevity; Proportional Hazards Models; Female; Biometry; laktace; biometrie; kvantitativní znak dědičný; Lactation; Česká republika; Cattle; ženské pohlaví; skot